The Role of Correctional Institutions in Fulfilling the Rights of Inmates Following the Issuance of Law No. 22 of 2022 Concerning Correctional Institutions (A Study at Class II A Correctional Institution in Pancur Batu) - Carles Darwin B, Zihono Zai; Herlina Manullang; Ojak Nainggolan (UNIVERSITAS PAKUAN, 2026)
Abstract This study examines the fulfillment of inmates' rights under Article 9 of Law No. 22 of 2022 on Correctional Systems at Class II A Pancur Batu Correctional Institution, and identifies structural barriers hindering their optimal implementation. Unlike prior studies focusing on single-issue rights, this research comprehensively evaluates all twelve mandated rights. Using an empirical legal approach, data were collected through interviews with five officers, questionnaires to thirty inmates via purposive sampling, and field observations, validated through triangulation. Findings confirm that the institution has substantially fulfilled all twelve rights through an operational health clinic, multi-faith worship facilities, nine vocational programs, and legal aid partnerships. However, four structural barriers persist: severe overcrowding at 52.5% excess capacity, limited infrastructure, a disproportionate staff-to-inmate ratio of 1:8.4, and the absence of a Buddhist religious partner. Cross-sectoral collaboration and national-level policy intervention are essential to fully realize the humane correctional vision of the law. Key Words: Inmates’ Rights, Correctional Institution, Law No. 22 of 2022, Overcrowding, Rights Fulfillment.